Analysis of Antenatal Care Compliance in the Event of Pregnancy Complications - Nurrahmah, Riska; Muliana, Nyanyak; Safrullah, Safrullah; Fajria, Leny (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: The high prevalence of maternal and infant mortality is still a problem that cannot be overcome. One effort to reduce maternal mortality and infant mortality is to carry out regular antenatal checks. Objective: This study aims to determine what perception factors influence compliance with Antenatal Care. Method: This type of research is quantitative correlative with a cross-sectional approach. Results and Discussion: The results of this study were that most respondents were in the non-compliant category in antenatal check-ups, 52.7%. The results of the correlation test show the P Value of perceived benefits with 0.001, perceived barriers 0.022, perceived susceptibility 0.016 and Cues to Action action cues 0.007. results of logistic regression analysis, the most dominant variable is perceived benefits with an odds ratio of 8.272. This non-compliance is caused by several factors that cause pregnant women not to receive antenatal care. Conclusion: In this study, the obstacles experienced by pregnant women include lack of knowledge about complications, access to transportation and economics as the main factors causing noncompliance with antenatal care. There is a significant relationship between the variables of perceived benefits, perceived barriers, perceived vulnerabilities, and action cues